The Mediating Role of Marketing Intelligence in Relationship Between Strategic Physiognomy and E-Service Delivery - Awad Jarallah, Mohammed; H. Ismail, Amjad; Sabeeh Lafta, Ahmed; Abdullah Amanah, Ahmed (Iraqi Journal for Administrative Sciences, 2026)
This study aims to discover the mediating role of Marketing Intelligence in enhancing the relationship between Strategic Physiognomy in its dimensions and the provision of E-Service Delivery. The study focuses on evaluating the methods used in collecting and analyzing data to identify challenges and opportunities in the Iraqi tourism environment. The study relied on environmental scanning to collect data on the problems facing the tourism sector in Iraq and analyze them to determine future trends. Advanced techniques and programs were used to collect and analyze information in line with the objectives, problem and questions of the study. The questionnaire was used as a means of obtaining information from the sample of (162) individuals in Iraqi tourism companies. The data were analyzed using statistical programs (Amos V.23), (SPSS V: 26(. The study concluded that there is a direct impact of Strategic Physiognomy in providing E-Service Delivery, and an indirect impact of Strategic Physiognomy in providing E-Service Delivery through adopting Marketing Intelligence. While the study reached a set of recommendations, the most important of which is that companies should use advanced analysis tools to collect and analyze data on markets, customers and competitors on a regular basis and train employees to use and benefit from them in making strategic decisions.